Analysis of Sirah Learning Model at MATSA, Malaysia and Dayah Darul Muta'allimin, Aceh: Between Traditional and Contemporary Educational Institutions - Muhammad Aulia; Khairuddin Hasan; Muhammad Iqbal; Mohd Lokman Bin Marzuki (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
The research aims to determine the depth of sirah material in MATSA, Malaysia, and Dayah Darul Muta'allimin, Aceh, collecting data related to the teaching sources used, methods used, media variations, and evaluation of learning implemented. The research uses a multi-site qualitative approach, with data collection techniques such as interviews, observations, and document studies. Data were collected using validated instruments. Data analysis involves data reduction, data presentation, and conclusion. The research results show that the scope of Sirah's learning material taught at the intermediate level is generally relatively similar. The teaching resource at MATSA, Malaysia, uses the book